PENGGUNAAN APLIKASI MULTIMEDIA PADA PEMBELAJARAN SENI BUDAYA DI SMKS INFORMATIKA AL-IHYA BANJARSARI - Bayu Eriga (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2017)
The use of multimedia applications on cultural arts learning at SMKS Informatics Al-Ihya Banjarsari. The purpose of this study is to discuss the use of multimedia applications in the process of art and culture learning. Multimedia technology makes learning more effective in conveying knowledge, skills and attitudes, as well as stimulating students' thoughts, feelings, attention and motivation, so teaching and learning activities become more interesting, meaningful and fun. The existence of multimedia technology is expected to explore and show the traditional cultural arts to be more modern than the various dimensions of both art and music art that can be applied in the learning of art and culture by utilizing various types of multimedia softwere applications.Key Word: Multimedia Applications, Media Learning, Art and Culture